Revisited "Muang Nimit" by Malai Chupinij - สัจจพันธุ์, รื่นฤทัย (Journal of the Faculty of Arts, Silpakorn University, 2019)
Muang Nimit is a novel written by Malai Chupinit with his pen name 'Riam Eng'. This utopian novel presents the idea of anti-war and the wish to have peaceful and happy society, although the story is set during World War II when the Japanese army invaded Thailand. The main theme of this novel is the awareness of the patriotism of Thais, in that on would sacrifice his life to keep freedom and to protect his motherland. With his masterly literary skills, Malai Chupimit narrated his novel by using the complex technique of metafiction. Also the conflicts in the mind of the main characters create deep and lively characters. This novel is distinguished because of the valuable message and the style of writing.